CURRENT ISSUES OF FORMATION OF LEGAL CONSCIOUSNESS AND CULTURE IN CIVIL SOCIETY (Archive of Conferences, 2021)
In this article, we talk about the fact that in our independent Uzbekistan, building a democratic, humane state governed by the rule of law and civil society, it is in this society that the development of legal culture, literally raising legal awareness has become a requirement of the times. Unless there is a high level of legal thinking in citizens and a position of a free individual who understands his behavior and responds to it consciously, various imbalances will arise.